2023
DOI: 10.15403/jgld-4893
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization of HCC/CCA Mixed Cancers in a Population-based Cohort

Abstract: Background and Aims: Primary liver cancer (PLC) ranks among of the most common cancers worldwide. Within this group, a minority of cases displays characteristics of both hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (iCCA), known as combined hepatocellular cholangiocarcinoma (cHCC- CCA). Currently, there is no specific standardized therapy for these mixed tumors. Therefore, the aim of our study was to analyze the clinical course, treatment and outcome of cHCC-CCA patients in a European pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The prognosis of patients who undergo resection for cHCC-CCA has been reported to vary across different studies, as shown in Table 1. 16,[45][46][47][48][49][50][51][52][53] Prognostic factors after cHCC-CCA resection include tumor diameter >5 cm, intrahepatic metastases, lymph node metastases, multifocality, vascular invasion, high levels of CA 19-9, incomplete capsule formation, and a resection margin of <2 cm. 15,54 One study conducted using data from the Surveillance, Epidemiology, and End Results Program (SEER) database found that liver transplantation (LT) did not provide any survival benefit compared with minor or major hepatectomy in 465 patients with cHCC-CCA.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…The prognosis of patients who undergo resection for cHCC-CCA has been reported to vary across different studies, as shown in Table 1. 16,[45][46][47][48][49][50][51][52][53] Prognostic factors after cHCC-CCA resection include tumor diameter >5 cm, intrahepatic metastases, lymph node metastases, multifocality, vascular invasion, high levels of CA 19-9, incomplete capsule formation, and a resection margin of <2 cm. 15,54 One study conducted using data from the Surveillance, Epidemiology, and End Results Program (SEER) database found that liver transplantation (LT) did not provide any survival benefit compared with minor or major hepatectomy in 465 patients with cHCC-CCA.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…In this issue of the Journal of Gastrointestinal and Liver Diseases, Teufel and collab. report a very large European population-based registry of liver tumors [14]. A series of 9,134 adult patients were diagnosed by histology between 2009 and 2020 in a German Clinical Cancer Registry database as HCC, iCCA and cHCC-CCA.…”
Section: Monica Acalovschimentioning
confidence: 99%